2018
DOI: 10.1111/odi.12993
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and developmental defects of enamel in individuals with chronic kidney disease: Systematic review and meta‐analysis

Abstract: Objective To evaluate studies assessing the prevalence of dental caries and developmental defects of enamel (DDE) in individuals with chronic kidney disease (CKD) in comparison with individuals without CKD. Materials and methods Electronic searches were performed in PubMed, Web of Science, Scopus, Medline via Ovid, and ProQuest databases from their inception date until February 2018. Two review authors independently selected the studies, extracted data, and assessed the methodological quality. Meta‐analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
13
0
2
Order By: Relevance
“…In a systematic review and meta-analysis by Limeira et al, caries prevalence in adults with CKD and in healthy controls was compared; these authors reported lower caries scores in CKD patients [32]. Similar findings of lower prevalence of caries were reported for children and adolescents with CKD in a systematic review by Andrade et al [33].…”
Section: Cariesmentioning
confidence: 76%
“…In a systematic review and meta-analysis by Limeira et al, caries prevalence in adults with CKD and in healthy controls was compared; these authors reported lower caries scores in CKD patients [32]. Similar findings of lower prevalence of caries were reported for children and adolescents with CKD in a systematic review by Andrade et al [33].…”
Section: Cariesmentioning
confidence: 76%
“…Without appropriate treatment, children with cystinosis can develop kidney failure. The pathophysiological alterations associated with kidney failure and its treatment can affect the development and the mineralization of teeth, such as enamel hypoplasia and has been associated with the production of poorly formed enamel as a result of ameloblast disruption …”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological alterations associated with kidney failure and its treatment can affect the development and the mineralization of teeth, such as enamel hypoplasia and has been associated with the production of poorly formed enamel as a result of ameloblast disruption. 17 This paper describes oral alterations in two renal transplant patients with NC and highlighting the rehabilitation dental treatment used in one of them.…”
Section: Introductionmentioning
confidence: 99%
“…Cinco estudos mostraram que indivíduos com IRC tinham uma prevalência significativamente maior de defeitos de esmalte do que indivíduos saudáveis. O autor concluiu que indivíduos com IRC apresentam menores pontuações de lesão de cárie dentária e maior prevalência de defeitos de esmalte em comparação com indivíduos saudáveis (Limeira et al, 2018). Costa et al (2017), as crianças que tiveram sucesso no TR mostram mudanças na composição salivar para a normalidade, portanto pode ter um risco maior de desenvolver cáries dentárias.…”
Section: Doença Cárieunclassified